Correction of Thread Position Mismatch in High Precision CNC Sewing - Stiebel, Tarek; Geller, Dieter; Merhof, Dorit (IEEE International Conference on Emerging Technologies and Factory Automation, ETFA, 2018)
Due to the elasticity of thread and tissue material, the stitches made by a computer program on a CNC sewing machine are shifted from their desired positions. The mismatch leads to a visually inferior appearance of the resulting thread pattern compared to the one intended by the manufacturer. This paper introduces a camera based inspection system that helps to find and evaluate the distortion vector for each individual stitch. These vectors can facilitate the automatic reprogramming of corrected stitch positions in the CNC sewing program to minimize the final distortion. An image processing pipeline is proposed, consisting of thread detection and model-based registration, finding an assignment of thread pixels and model stitch positions. The corresponding distortion vectors are computed for every individual stitch.
CRIS-Team Scopus Importer:2023-03-23
Keywords: High Precision Sewing; Quality Assurance; Stitch Pattern Detection